A subset of calcium‐binding S100 proteins show preferential heterodimerization. (21st February 2019) - Spratt, Donald E.; Barber, Kathryn R.; Marlatt, Nicole M.; Ngo, Vy; Macklin, Jillian A.; Xiao, Yiming; Konermann, Lars; Duennwald, Martin L.; Shaw, Gary S.
Abstract : The assembly of proteins into dimers and oligomers is a necessary step for the proper function of transcription factors, muscle proteins, and proteases. In uncontrolled states, oligomerization can also contribute to illnesses such as Alzheimer's disease. The S100 protein family is a group of dimeric proteins that have important roles in enzyme regulation, cell membrane repair, and cell growth. Most S100 proteins have been examined in their homodimeric state, yet some of these important proteins are found in similar tissues implying that heterodimeric molecules can also be formed from the combination of two different S100 members. In this work, we have established co‐expression methods in order to identify and quantify the distribution of homo‐ and heterodimers for four specific pairs of S100 proteins in their calcium‐free states. The split GFP trap methodology was used in combination with other GFP variants to simultaneously quantify homo‐ and heterodimeric S100 proteins in vitro and in living cells. For the specific S100 proteins examined, NMR, mass spectrometry, and GFP trap experiments consistently show that S100A1:S100B, S100A1:S100P, and S100A11:S100B heterodimers are the predominant species formed compared to their corresponding homodimers. We expect the tools developed here will help establish the roles of S100 heterodimeric proteins and identify how heterodimerization might alter the specificity for S100 protein action in cells. Abstract : S100 proteins are dimeric calcium‐binding proteins with important roles in membrane repair, a process that is altered in some neurological diseases. Different members of the S100 group show overlapping tissue expression, implying that these proteins might exist as homo‐ and heterodimers. We examined select members and combinations of S100 proteins and demonstrated that a preference exists for heterodimeric S100 proteins.